Avoidable 30‐day readmissions in patients undergoing vascular surgery. Issue 6 (2nd August 2019) - Knighton, A.; Martin, G.; Sounderajah, V.; Warren, L.; Markiewicz, O.; Riga, C.; Bicknell, C.
Abstract : Background: Vascular surgery has one of the highest unplanned 30‐day readmission rates of all surgical specialties. The degree to which these may be avoidable and the optimal strategies to reduce their occurrence are unknown. The aim of this study was to identify and classify avoidable 30‐day readmissions in patients undergoing vascular surgery in order to plan targeted interventions to reduce their occurrence, improve outcomes and reduce cost. Methods: A retrospective analysis of discharges over a 12‐month period from a single tertiary vascular unit was performed. A multidisciplinary panel conducted a manual case‐note review to identify and classify those 30‐day unplanned emergency readmissions deemed avoidable. Results: An unplanned 30‐day readmission occurred in 72 of 885 admissions (8·1 per cent). These unplanned readmissions were deemed avoidable in 36 (50 per cent) of these 72 patients, and were most frequently due to unresolved medical issues (19 of 36, 53 per cent) and inappropriate admission with the potential for outpatient management (7 of 36, 19 per cent). A smaller number were due to inadequate social care provision (4 of 36, 11 per cent) and the occurrence of other avoidable adverse events (4 of 36, 11 per cent). Conclusion: Half of all 30‐day readmissions following vascular surgery are potentially avoidable. Multidisciplinary coordination of inpatient care and the transition from hospital to community care after discharge need to be improved. Abstract : Fifty per cent of all unplanned 30‐day readmissions in patients undergoing vascular surgery are potentially avoidable. To reduce this burden, there is a need to take a multidisciplinary approach to optimizing medical care, support the transition from hospital to community care effectively, and develop targeted strategies to patients deemed to be at high risk. Many readmissions avoidable Abstract : Antecedentes: La cirugía vascular tiene una de las tasas más elevadas de reingresos no planificados a los 30 días de todas las especialidades quirúrgicas. Se desconoce hasta qué punto este problema puede ser evitable y las estrategias óptimas para su disminución. El objetivo de este estudio fue identificar y clasificar los reingresos evitables a los 30 días en pacientes sometidos a cirugía vascular para planificar intervenciones dirigidas a su disminución, mejorar los resultados y reducir el coste. Métodos: Se realizó un análisis retrospectivo de las altas hospitalarias durante un periodo de 12 meses en una unidad vascular terciaria. Un panel multidisciplinario realizó una revisión manual de los casos para identificar y clasificar aquellos reingresos urgentes no planificados a los 30 días que se considerasen evitables. Resultados: Se registró un reingreso no planificado a los 30 días en 72/885 (8, 1%) ingresos. Estos reingresos no planificados fueron considerados evitables en el 50, 0% (36/72) y fueron debidos con más frecuencia a cuestiones médicas sin resolver (19/36, 52, 8%) y a un ingreso no apropiado con la posibilidad de tratamiento ambulatorio (7/36, 19, 4%). En un número menor de casos se debió a una asistencia social inadecuada (4/36, 11, 1%) y la aparición de otros eventos adversos evitables (4/36, 11, 1%). Conclusión: La mitad de los reingresos a los 30 días en pacientes vasculares son potencialmente evitables. Tras el alta hospitalaria debe mejorarse la coordinación multidisciplinaria de la atención hospitalaria y la transición desde el hospital a la atención comunitaria.